Home Away from Home: International Students and their Identity-Based Social Networks in Australia - Gomes, Catherine; Berry, Marsha; Alzougool, Basil; Chang, Shanton (Journal of International Students, 2014)
This paper explores the role of identity in helping international students form social networks at an Australian institution and how these networks contribute to creating a sense of home away. The findings suggest that international students form distinct social networks that are not necessarily solely made up of fellow students from their home countries. Rather, international students form a mixture of social networks that are based on the complex individual identities of each student centred on a variety of common factors, such as: course of study, place of work, neighbourhood, culture, religion and personal interests (hobbies). Hence many students are part of social groups that consist of international students from their specific region and beyond, as well as local (Anglo and non-Anglo) students. These locally based social networks complement existing home-based networks which are maintained virtually through social media to create a home away from home.